2022
DOI: 10.1177/00208728221112731
|View full text |Cite
|
Sign up to set email alerts
|

Global social work working conditions and wellbeing

Abstract: This research explores the working conditions of social workers around the globe, using a mixed-methods approach. A survey of working conditions and wellbeing was distributed to social workers via email and social media. Results subsequently informed the interview schedule for individual semi-structured interviews with social work leaders from across the world. Results confirm that social workers have among the most difficult working conditions of all equivalent professions, with detrimental effects on service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Several studies have indicated that the demand that influences teachers' well‐being the most is workload, which involves a considerable amount of admin and paperwork, extent of non‐teaching tasks, loss of non‐class contact time, large class sizes, and lack of support within the classroom and a more heterogeneous student population (Butt & Lance, 2005; Hakanen et al, 2006; Ravalier & Walsh, 2017). Furthermore, workload could cause work–life conflict (WLC) being an extension of work–family conflict, reflecting the reality that the work role may interfere with individuals' other personal life roles and interests (Kossek, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that the demand that influences teachers' well‐being the most is workload, which involves a considerable amount of admin and paperwork, extent of non‐teaching tasks, loss of non‐class contact time, large class sizes, and lack of support within the classroom and a more heterogeneous student population (Butt & Lance, 2005; Hakanen et al, 2006; Ravalier & Walsh, 2017). Furthermore, workload could cause work–life conflict (WLC) being an extension of work–family conflict, reflecting the reality that the work role may interfere with individuals' other personal life roles and interests (Kossek, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Hakanen et al, 2006; Harmsen et al, 2019; Tadić et al, 2015). Results of research done on SWB have indicated, among other things, that workload in teachers is negatively associated with job satisfaction (JS) and that having autonomy and exchange with the manager is positively correlated with JS (Ravalier & Walsh, 2017). Albeit, this research exclusively focused on JS and did not incorporate emotions, an essential part of SWB.…”
Section: Introductionmentioning
confidence: 99%
“…Social workers report the negative impacts of working in this context, including low job satisfaction and retention (e.g., Antonopoulou et al, 2017; BBC, 2021). Amongst workers, burnout is a frequent complaint (Gibbons et al, 2011; Hussein, 2018; Ravalier & Boichat, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They have a responsibility for the wellbeing and mental health of their students (Scottish Government, 2021) and a requirement to be trauma informed (NHS Health Scotland 2017; NHS Education for Scotland, 2020). They have oversight of the social and emotional needs of their pupils and families (Scottish Executive, 2006;Scottish Government, 2014) which can provide a greater level of emotional demand on them (Hanley, 2017;Ravalier & Walsh, 2017). It has therefore been argued that to expect this level of social and emotional engagement from teachers, without providing a safe reflective space, could be problematic for them as individuals and for the education system as a whole (Reid & Soan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To address these tensions, many have advocated for PRS as a space to be able to share the emotional load with someone outside of the school. Someone who can hold and contain the level of emotion felt and provide a safe space to explore issues and to rehearse different ways of understanding and managing them (Ravalier & Walsh, 2017;Lawrence, 2020;Bainbridge et al, 2022). This proposition has been further strengthened by the impact of the recent pandemic (Connor et al, 2022), which has provided the catalyst to bring into mainstream discussions the possibility of PRS being more regularly provided in schools, as the increasing pressure on staff to keep children safe and improve, not only their academic skills and successes, but also Is there a felt need from head teachers to support their wellbeing through the offer of professional reflective supervision?…”
Section: Introductionmentioning
confidence: 99%